A Portrait of Palestinians in Mahmoud Darwish’s Poem ‘Qasidatu Al-Ardi’: New Historicism Analysis - Qowlits Tsabita, Qonita Qorrie Aini; Arief Rahman Hakim (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to elucidate the meaning of the poem "Qasidatu al-Ardi" by Mahmoud Darwish through the lens of Stephen Greenblatt's new historicism perspective. This research is categorized as descriptive qualitative research. The primary data sources for this study include the poem "Qasidatu al-Ardi" and relevant non-literary texts, which comprise books and associated websites. The data collection technique employed in this study involves a reading approach that applies Greenblatt's new historicism perspective, emphasizing the simultaneous analysis of literary and non-literary texts to explore their interrelationship. The analysis techniques utilized include data reduction, data presentation, and drawing conclusions. The study reveals that the depiction of the Palestinian people's struggle in the poem "Qasidatu al-Ardi" is intricately linked to the historical context of Land Day in 1976 in Galilee. Furthermore, the poem presents the condition of the Palestinian people through themes of Palestinian nationalism, genocide in the Palestinian territories, and the aspirations of the Palestinian populace. Abstrak Penelitian ini bertujuan untuk mengungkap makna puisi “Qasidatu al-Ardi” karya Mahmoud Darwish dengan berdasar new historicism perspektif Stephen Greenblatt. Jenis penelitian ini adalah penelitian kualitati deskriptif. Adapun sumber data penelitian ini adalah puisi “Qasidatu al-Ardi” karya Mahmoud Darwish, dan teks non-sastra berupa buku dan website yang relevan. Teknik pengumpulan data dalam penelitian ini menggunakan teknik baca cata dengan menerapkan pendekatan new historicism perspektif Stephen Greenblatt. Pendekatan ini menekankan pada pembacaan secara bersamaan antara teks sastra dengan teks non-sastra untuk mengetahui keterkaitan antara keduanya. Adapun teknik analisis yang digunakan adalah reduksi data, penyajian data, dan kesimpulan. Hasil penelitian mengenai  bentuk perjuangan rakyat Palestina dalam puisi “Qasidatu al-Ardi” menunjukkan bahwa: penciptaan puisi “Qasidatu al-Ardi” berkaitan erat dengan latar belakang sejarah Land Day tahun 1976 di Galilea; dan kondisi rakyat Palestina dalam puisi ini ditunjukkan melalui adanya bentuk nasionalisme rakyat Palestina, genosida di wilayah Palestina, dan harapan rakyat Palestina.